Upaya Guru Pendidikan Agama Islam dalam Mengatasi Perilaku Bullying di Antara Peserta Didik - Basri, Junaidin; Salamudin, Ceceng; Hardiansyah, Asep Wisnu (MASAGI : Jurnal Pendidikan Agama Islam, 2025)
Bullying remains a widespread phenomenon in Indonesia, including in educational settings. Observations by researchers and Islamic Religious Education (PAI) teachers indicate that bullying has occurred at school, taking various forms. Guidance and Counseling (BK) data from school in 2024 recorded that the dominant forms of bullying were verbal (40%), relational (30%), cyberbullying (20%), and physical (10%). This situation underscores the importance of Islamic Religious Education (PAI) teachers in understanding the various efforts made to address bullying in schools. This study aims to describe the forms of bullying behavior and the efforts of Islamic Religious Education (PAI) teachers in overcoming bullying behavior at school. This research used a descriptive qualitative approach with a case study method. Data collection techniques included interviews, observation, and documentation. Both primary and secondary data sources were used. Data analysis involved four stages: data collection, data reduction, data presentation, and conclusion drawing. The results showed that bullying behavior at school encompassed three forms: verbal bullying in the form of teasing, relational bullying in the form of exclusion, and cyberbullying, namely teasing on social media. Islamic Religious Education teachers addressed these issues through two approaches: preventive measures, integrating Islamic values ​​into learning, increasing religiosity through religious activities, and implementing the P5 program. Curative measures, including personal counseling, providing advice and role models, implementing educational sanctions, and collaborating with parents. Keywords: bullying, pai teachers' efforts, students